Determinação de hidrocarbonetos aromáticos policíclicos (HPAs) em alimentos obtidos por técnicas diferentes. - Guimarães, Artemizia Pessoa (2014)
Polycyclic aromatic hydrocarbons (PAHs) are a class of organic compounds that consist of carbon and hydrogen atoms in aromatic ring structures. The PAHs are produced from incomplete combustion of organic material and can be considered persistent organic pollutants. They present mutagenic and carcinogenic activities, which cause negative impacts on human health and the environment. Food represents an important source of exposure to these compounds. Foods contaminations can occur due to processing such as smoking, roasting and direct drying with wood, air and air pollution. water and the presence of PAHs in soils. The present study aimed to study the extraction of PAHs in two types of fruits: cashew (Anacardium occidentale) and tomatoes (Lycopersicum esculentum), using the following techniques: Solid Phase Matrix Dispersion (DMFS) and Soxhlet extraction. The analysis of identification and quantification of PAHs were performed by gas chromatography with mass detection (GC-MS). The methodology used also involved the validation of the PAHs extraction and analysis methods in organic matter. The validated methods were applied to the samples of interest. The methodology used presented good results of recovery, precision, limit of detection (LD) and quantification (LQ) for the analyzed PAHs. For this study, the LD ranged from 6.71 to 76.12 μgL-1 and the LQ ranged from 22.36 to 253.73 μgL-1. These results are in agreement with the literature. The study of linearity generated results with a correlation coefficient greater than 0.99, which fits the recommendations of the National Health Surveillance Agency and the National Metrology Institute. Extractions of PAHs from cashew and tomato samples were performed using the Soxhlet and DMFS methods, at concentrations of 20, 50 and 100 μgL-1. In general, the PAHs recovery was more efficient with increasing the concentration. For the Soxhlet method, the results obtained also showed that the recovery was more efficient for tomato samples. The DMFS method proved to be more appropriate for the fruit samples analyzed because it was possible to recover the 16 PAHs analyzed in higher percentages than by the Soxhlet method.